Non-orthogonal basis sets for hyperspherical coordinate calculations on chemical reactions - Pogrebnya, S; Richardson, A; Clary, D (2001)
In quantum reactive scattering calculations using hyperspherical coordinates a problem can arise in calculating Hamiltonian matrix elements between non-orthogonal basis functions from different reaction arrangement channels. The calculation of these matrix elements is considered here. It is shown that the use of particle-in-a-box functions defined within a limited interval requires special care in treating the kinetic energy operator. © 2001 Elsevier Science B.V.